St Peter-on-the-Wall: Landscape and Heritage on the Essex Coast - Christie, Neil (Medieval Settlement Research, 2023)
The cover of this volume immediately grabs the reader with an evocative aerial (drone?) view looking from coastal mudflats towards a flat, farmed landscape with intermittent hedge-lines, preceded by grazing-marsh and with a wooden observation tower for viewing local birdlife. On the margin between natural and farmed stands an isolated structure, namely the chapel of St Peter, whose construction dates back to the seventh century in the context of the progressive expansion of Christianity in Anglo-Saxon England. Key in this was the establishment of a set of churches as beacons of the faith in diverse former Roman sites, starting in Canterbury at the time of the Augustinian mission (promoted by Rome), and then with a notable installation of churches and monks in abandoned forts belonging to the late Roman ‘Saxon Shore’ network, which extended from Portchester in the south to Brancaster in Norfolk, and encompassing sites like Richborough and Reculver in Kent, and Walton Castle in Suffolk. St Peter’s Chapel was inserted over a gatehouse at the ‘central’ fort of Orthona (called by Bede when writing in the 730s the civitas of Ythancæstir), near modern Bradwell-on-Sea in Essex, sited in the Dengie parish and facing the Blackwater Estuary. Bede relates, however, that the Ythancæstir foundation was led by St Cedd in 654 as part of a Northumbrian mission to the East Saxons; Cedd subsequently transferred, with 30 monks, to a northern base at Lastingham in Yorkshire. One argument holds that the extant chapel is in fact a ‘second-generation church founded after 669, when Archbishop Theodore of Canterbury brought the kingdom of Essex under the influence of the Roman church emanating from Kent’ (p.136). While the available archaeology is not sufficient to solve this argument, a seventh-century origin is not in doubt.